الرواة الضعفاء والمجهولون والمتكلم فيهم الذين انفرد ابن ماجة بالرواية عنهم عن أصحاب الكتب الخمسة "البخاري، ومسلم، وأبي داود، والترمذي، والنسائي" : دراسة نقدية - عباس، ستار محمد (2009)
Ibn Majah is one of those who wrote the Six Books and who had gathered the hadiths of the Messenger Muhammad (P.B.U.H) arranged in accordance with the categories of Fiqh . Ibn Majah is distinguished among narrators by the number of hadiths which he narrates and the number of hadiths' men for whom he narrates. For this reason his book is highly considered, compared with other books of hadith, such as Muwatta' Malik, Sunan Al-Darmi, and others. The Boseeri had written a book tackling those men for whom Ibn Majah had alone narrated. He distinguished between the correct and weak hadiths in his book titled "Misbah Al-Zujajah fi Zawaid Ibn Majah". As for the men of hadith for whom Ibn Majah alone had narrated, as far as I know, no one has written about them. So, this study is dedicated for those aforementioned narrators. I distinguished between those who are trusted and those who are weak in narration, according to Al-Thahabi and Ibn Hajar. The results were as follows: 1- The number of narrators for whom Ibn Majah alone had narrated is around (825). 2- The trusted narrators are (433). 3- The weakened narrators are (392(. The latter were the concern of my study. Through carrying out my research, I found that those narrators are not all weak, despite what had been said about some of them. Moreover, weak narrators are not all in the same level of weakness. Some of them are possibly weak; some others are unknown; and others are neglected and liars. They were as follows: o The narrators whom were disputed among the scholars of Jarh and Ta'deel, concerning being trusted or distrusted and they are mostly trusted, are (91) narrators. o The narrators whom were disputed among the scholars of Jarh and Ta'deel, concerning being trusted or distrusted, and they are mostly weak, are (80) narrators. However, their weakness is probable. o The unknown narrators are (135). o The narrators who are neglected and liars, and whose weakness is undisputable, are (86(.